Identifying the factors affecting financial condition of Malaysia - Pang, Yee-Ling; Lee, Hock Ann (Universiti Malaysia Sarawak, 2021)
This research focuses on the domestic and external determinants of Malaysia’s financial condition, ranging from January 2003 and March 2019. To represent the domestic determinants, a total amount of twelve financial indicators are adopted to compute three indices using the Principal Component Approach (PCA). Three of the indices embody three respective financial segments, particularly the banking system, the foreign exchange market, and the capital market within the Malaysian financial system. These three segments offer a glimpse of the Malaysian financial condition. For the external determinant, the US total assets of all Federal Reserve Banks are adopted as the proxy for the size of the US balance sheet. This research intends to evaluate the validity of the long-run association and its corresponding level of effect between the computed indices and the US balance sheet size via the conduct of the ARDL bounds test approach. The research findings have verified the validity of the long-run association between the Malaysian financial condition and the US balance sheet size. There is a substantial role played by the US balance sheet size in affecting the well-being of Malaysian financial condition, given the statistical significance is shown in the association between the US balance sheet size and the financial-segment-based indices, whereby its strongest influence is found on the banking system condition.